Emotion in the Tudor court: literature, history, and Early Modern feeling - Irish, Bradley J. (Rethinking the Early Modern, 2018)
"Contents" -- "Acknowledgments" -- "List of Abbreviations" -- "Introduction" -- "Chapter 1. The Disgusting Cardinal Thomas Wolsey" -- "Chapter 2. The Envious Earl of Surrey" -- "Chapter 3. The Rejected Earl of Leicester, the Rejected Sir Philip Sidney" -- "Chapter 4. The Dreading, Dreadful Earl of Essex" -- "Notes